ANALISIS RHODAMIN B PADA SAUS TOMAT YANG BEREDAR DI KOTA MADIUN DENGAN METODE KROMATOGRAFI LAPIS TIPIS - Pranita Nurdiana Agustin; Ani Sulistyarsi; Sri Utami (UNIVERSITAS PGRI MADIUN, 2016)
Rhodamin is one of additional food ingredient which often used to recolour the food.The additional food ingredient contains carsinogenic which can affect our health with a cancer asthat ingredient is not acceptable ingredient for food. Unfortunately,many Indonesian do not knowwhether the syntetical ingredients can be used or that is being prohibited to use. The purpose ofthis research is not only to observe whether there is Rhodamin B inside the tomato sauces aroundMadiun, but also to get the result of the analysis as the mateial for aditif subtance experiment inBio-chemical lesson. Furthermore, this descriptive qualitative research used non randomsampling as its technique. The sample is taken from pentol seller, mie ayam seller and baksoseller. The samples are being analyzed with Kremtografi Lapis Tipis (KLT). The result of theanalysis showed that all of the sample is negative. On the other hand, there is no Rhodamin B onit. The indicated sample has the same Rf with Rhodamin B. It will change it color into red as itsresponse toward H2SO4 and HCl. The sample also being compared with wantex. The resultshowed that the Rf samples had A3, A4, A5, B4, B5,C1, C2, C3, C4 dan C5. Based on the result,the assumption of the samples is that the samples have wantex material on it